De novo transcriptome sequencing and gene co-expression reveal a genomic basis for drought sensitivity and evidence of a rapid local adaptation on Atlas cedar (Cedrus atlantica) - Cobo-Simón, Irene; Gómez-Garrido, Jèssica; Esteve-Codina, Anna; Dabad, Marc; Alioto, Tyler; Maloof, Julin N.; Méndez-Cea, Belén; Seco, José Ignacio; Linares, Juan Carlos; Gallego, Francisco Javier (Frontiers in Plant Science, 2023)
Understanding the adaptive capacity to current climate change of drought-sensitive tree species is mandatory, given their limited prospect of migration and adaptation as long-lived, sessile organisms. Knowledge about the molecular and eco-physiological mechanisms that control drought resilience is thus key, since water shortage appears as one of the main abiotic factors threatening forests ecosystems. However, our current background is scarce, especially in conifers, due to their huge and complex genomes. Here we investigated the eco-physiological and transcriptomic basis of drought response of the climate change-threatened conifer Cedrus atlantica. We studied C. atlantica seedlings from two locations with contrasting drought conditions to investigate a local adaptation. Seedlings were subjected to experimental drought conditions, and were monitored at immediate (24 hours) and extended (20 days) times. In addition, post-drought recovery was investigated, depicting two contrasting responses in both locations (drought resilient and non-resilient). Single nucleotide polymorphisms (SNPs) were also studied to characterize the genomic basis of drought resilience and investigate a rapid local adaptation of C. atlantica. De novo transcriptome assembly was performed for the first time in this species, providing differences in gene expression between the immediate and extended treatments, as well as among the post-drought recovery phenotypes. Weighted gene co-expression network analysis showed a regulation of stomatal closing and photosynthetic activity during the immediate drought, consistent with an isohydric dynamic. During the extended drought, growth and flavonoid biosynthesis inhibition mechanisms prevailed, probably to increase root-to-shoot ratio and to limit the energy-intensive biosynthesis of secondary metabolites. Drought sensitive individuals failed in metabolism and photosynthesis regulation under drought stress, and in limiting secondary metabolite production. Moreover, genomic differences (SNPs) were found between drought resilient and sensitive seedlings, and between the two studied locations, which were mostly related to transposable elements. This work provides novel insights into the transcriptomic basis of drought response of C. atlantica, a set of candidate genes mechanistically involved in its drought sensitivity and evidence of a rapid local adaptation. Our results may help guide conservation programs for this threatened conifer, contribute to advance drought-resilience research and shed light on trees' adaptive potential to current climate change.